LES PHILOSOPHIES DU HYGGE : ENTRE HÉRITAGE CULTUREL ET DÉVELOPPEMENT PERSONNEL FACE À LA QUÊTE HYPERMODERNE DU BIEN-ÊTRE INDIVIDUEL - Camille ROELENS (Studia Universitatis Babeș-Bolyai. Philosophia)
Hygge Philosophies: Between Cultural Heritage and Personal Development in the Face of the Hypermodern Quest for Individual Well-Being. In this article, we are interested in hygge, often presented as a Danish philosophy of life. We question hygge as it is portrayed and listed in personal development literature (1). We suggest that, in the contemporary Western democratic context, hygge touches on both a part of Danish cultural heritage and a sphere of concerns typical of Western democratic hypermodernity (2). A concluding section will allow us to make some generalizations about the stakes of intellectual work in our societies in the XXIst century and the contributions that philosophers can make (3).